-3=3k-9

Simple and best practice solution for -3=3k-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3=3k-9 equation:



-3=3k-9
We move all terms to the left:
-3-(3k-9)=0
We get rid of parentheses
-3k+9-3=0
We add all the numbers together, and all the variables
-3k+6=0
We move all terms containing k to the left, all other terms to the right
-3k=-6
k=-6/-3
k=+2

See similar equations:

| 13x+5x=12 | | k/9-29=41 | | 15+5x=4(−x+3)−24 | | 4u+8=5 | | 7t-5t=10 | | 3/2x+4=19 | | 7w+35=42 | | 11-3=c-4 | | 35n-162=468 | | –738=d+–1 | | 4x−3=2x | | (2/3)x+4=(5/3)x | | x+0.2x=117 | | -6x-4=34 | | 3/4x-4=56 | | -6x-4=-31 | | a-1=11-7 | | 8.5=-5z | | -7+7x=49 | | 2x/5=-60 | | 2(4x-5=2 | | 2+5c=22 | | -9(v-5)=7v+29 | | 20-6n=54 | | 2n-6n=54 | | b×(-7.8)=-79.56 | | 178x=(x-2)180 | | |2x-4|=0 | | 13-4=c-5 | | 25n-234=126 | | 4x+4+5x-3=0 | | (12+2u)+3=10.23 |

Equations solver categories